Principal/Madrasah Management in the Financial Management System - Cipto Handoko; Tukiran Tukiran (Universitas Pahlawan Tuanku Tambusai, 2022)
Management is one of the main elements in the success of an activity, there is no field in the field of Education. Student Operational Assistance (BOS) is one part of the school to be managed optimally to obtain maximum common goals. This paper aims to implement the application of financial management in education, especially in BOS. The type of research used includes descriptive qualitative research with an ethnographic approach. The results of the study illustrate that in the implementation of school financial management, especially the management of BOS funds, it is carried out in several stages of planning involving various stakeholders, implementation, monitoring and evaluation.